TLR2 2029C/T and TLR3 1377C/T and −7C/A Polymorphisms Are Associated with the Occurrence of Abdominal Aortic Aneurysm - Jabłońska, Agnieszka; Zagrapan, Branislav; Neumayer, Christoph; Klinger, Markus; Eilenberg, Wolf; Nanobachvili, Josif; Paradowska, Edyta; Brostjan, Christine; Huk, Ihor (The Journal of immunology (1950), 2020)
TLRs are a family of signaling sensors that play a crucial role in the host immune response and are involved in the modulation of inflammatory processes. To study their contribution to abdominal aortic aneurysm (AAA) formation and development, we determined the frequency of TLR2, TLR3, TLR4, and TLR9 single-nucleotide polymorphisms (SNPs) and investigated the association between polymorphisms and the risk of AAA incidence. A total of 104 patients with AAAs and 112 healthy, unrelated volunteers were screened for the presence of TLR2 (2029C/T and 2258G/A), TLR3 (1377C/T, 1234C/T, and −7C/A), TLR4 (896A/G, 1196C/T, and 3266G/A), and TLR9 (−1237T/C, −1486T/C, 1174G/A, and 2848C/T) SNPs by using PCR-RFLP analysis. The heterozygous genotype of the TLR2 2029C/T SNP was more common in patients with AAA than in healthy subjects (p < 0.0001) and was associated with at least an 8-fold increased risk of AAA incidence (p < 0.001). The wild-type genotype of the TLR3 −7C/A SNP was associated with a 3-fold increased risk of hypertension (p = 0.026). The heterozygous TLR3 genotype 1377C/T and −7C/A SNPs were less common in patients with AAA than in healthy subjects (p < 0.0001 and p = 0.0004, respectively) and were associated with a decreased risk of AAA occurrence (p < 0.001 and p = 0.0012, respectively). No relation to AAA risk was found for TLR4 SNPs. Heterozygous genotypes of the TLR2 2029C/T and TLR3 1377C/T and −7C/A SNPs may serve as genetic biomarkers of AAA incidence.